On the Scientific Method and Social Sciences - S. Ali Seyyedifard (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Amongst long standing, and sometimes vexing debates around the scientific method, the explication and analysis of the concept of method received scant attention. In this paper, I have tried to suggest a clear account of the method. My proposed account is closely tied to the concepts of “descriptive ought/ought not” and “cognitive purposes.” In consequence, I have pinned down these two concepts. In the next section, I have indicated how logic is related to the scientific method. According to my suggestion, the logic differs from the scientific method in that the former fulfills a more general and comprehensive cognitive purpose than the latter. Logic is a precondition for gaining any sort of knowledge, that is, knowledge as such. On the contrary, the scientific method is required to obtain proper knowledge in a specific domain. Then, I have considered the sorts of relations there might be between ethics and the scientific method. In the last section, I have got into considering what my suggestions yield to when applied to social science.